2018
DOI: 10.1080/15402002.2018.1545652
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Associates With Recent Nonsuicidal Self-Injury Engagement in Adolescents

Abstract: Objective/Background: Poor sleep has been shown to have multiple negative outcomes during adolescence, in both academic and mental health domains. Several studies have identified the association between poor sleep and suicide risk in adolescents. However, onset of and engagement in nonsuicidal self-injury (NSSI) is also common in this age group, but this behavior has rarely been studied in association with sleep in adolescent samples. In the current study, it was expected that poorer sleep and more symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…A handful of longitudinal studies partially supported these findings, where sleep difficulties, and particularly insomnia, predicted later engagement in NSSI (Bandel & Brausch, 2020;Junker, Bjørngaard, Gunnell, & Bjerkeset, 2014;Lundh et al, 2013;Wong et al, 2011). However, this link disappeared when controlling for previous psychopathology (Bandel & Brausch, 2018;Junker et al, 2013). Although informative, these studies have limitations.…”
Section: Sleep Difficulties and Nssimentioning
confidence: 93%
See 1 more Smart Citation
“…A handful of longitudinal studies partially supported these findings, where sleep difficulties, and particularly insomnia, predicted later engagement in NSSI (Bandel & Brausch, 2020;Junker, Bjørngaard, Gunnell, & Bjerkeset, 2014;Lundh et al, 2013;Wong et al, 2011). However, this link disappeared when controlling for previous psychopathology (Bandel & Brausch, 2018;Junker et al, 2013). Although informative, these studies have limitations.…”
Section: Sleep Difficulties and Nssimentioning
confidence: 93%
“…Cross‐sectional studies show that adolescents who self‐injured also reported sleep difficulties, including symptoms of insomnia (Hysing, Sivertsen, Stormark, & O'connor, 2015; Liu, Chen, Bo, Fan, & Jia, 2017; McGlinchey, Courtney‐Seidler, German, & Miller, 2017). A handful of longitudinal studies partially supported these findings, where sleep difficulties, and particularly insomnia, predicted later engagement in NSSI (Bandel & Brausch, 2020; Junker, Bjørngaard, Gunnell, & Bjerkeset, 2014; Lundh et al., 2013; Wong et al., 2011). However, this link disappeared when controlling for previous psychopathology (Bandel & Brausch, 2018; Junker et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…A positive relationship has been confirmed in adolescents. 89 Sleep disorders have been found to play a causal role in emotional dysfunction problems. In particular, sleep disorders inhibit the function of sleep in processing emotions.…”
Section: Comorbidity Of Borderline Personality Disorder and Insomniamentioning
confidence: 99%
“…Notably, most individuals engage with NSSI to regulate intense emotions, and sleep disorders may increase susceptibility to NSSI by contributing to dysregulated emotions. 89 …”
Section: Comorbidity Of Borderline Personality Disorder and Insomniamentioning
confidence: 99%
“…Furthermore, poor sleep in adolescents has been associated with a wide range of negative outcomes including but not restricted to: obesity (Sivertsen et al, 2014b); low mood (Dahl and Harvey, 2007;McGlinchey et al, 2017;Sivertsen et al, 2014a), poor emotional regulation (Baum et al, 2014) and general self-regulation (Owens et al, 2016); anxiety and internalising disorders (Babson et al, 2010;Dahl and Harvey, 2007;McMakin and Alfano, 2015); hopelessness (Winsler et al, 2015); suicidality (Chiu et al, 2018); self-harm (Bandel and Brausch, 2020;Hysing et al, 2015;Liu et al, 2017); and poor concentration and academic performance (Dewald et al, 2010;O'Brien, 2011). Conversely, good sleep has been found to be associated with improved physical and psychological wellbeing (Segura-Jiménez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%